2011
DOI: 10.1111/j.1464-410x.2011.10812.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood loss during radical prostatectomy: impact on clinical, oncological and functional outcomes and complication rates

Abstract: What ' s known on the subject? and What does the study add?It is generally accepted in the medical community that total and intra-operative blood loss after RALP is signifi cantly lower in comparison with ORRP. This has led to speculation that less bleeding results in better visualization of the operative fi eld resulting in superior potency and continence.Blood loss (BL) during ORRP does not adversely impact clinical and functional outcomes irrespective of how BL is defi ned. Thus, the lower BL associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Despite the introduction of laparoscopy (including robotic-assisted approaches), open radical retropubic prostatectomy is still the standard surgical treatment for localized prostate cancer (4, 7-11). The historical gold standard of transurethral resection of prostate (TURP), which is an effective procedure, is still associated with the risk of intraoperative and postoperative bleeding (2, 12-14). …”
Section: Introductionmentioning
confidence: 99%
“…Despite the introduction of laparoscopy (including robotic-assisted approaches), open radical retropubic prostatectomy is still the standard surgical treatment for localized prostate cancer (4, 7-11). The historical gold standard of transurethral resection of prostate (TURP), which is an effective procedure, is still associated with the risk of intraoperative and postoperative bleeding (2, 12-14). …”
Section: Introductionmentioning
confidence: 99%
“…In RP, dissection of the posterior surface of the prostate is performed at the layer between the rectum and DF, and the prostate is removed with DF [15]. In our study at the midpoint of the prostate posterior, the DF fused with the PC in 94 % of the case.…”
Section: Discussionmentioning
confidence: 66%
“…The RP (open surgery, laparoscopy or robotic-assisted procedures) allows the dissection and identification of the different fasciae surrounding the prostate and the preservation of the neurovascular bundles [15]. However, fascial dissection remains conditioned by oncologic radicality, tumor location, size and Gleason score.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies comparing RALP with retropubic radical prostatectomy have found that RALP reduces blood loss during surgery [3, 68]. Typical blood loss during RALP at our institution is less than 300 mL, including that passed through the urine.…”
Section: Discussionmentioning
confidence: 96%